2020
DOI: 10.31545/intagr/126439
|View full text |Cite
|
Sign up to set email alerts
|

Response of maize and black gram yield and water productivity to variation in canopy temperature and crop water stress index

Abstract: In order to evaluate the ability of the crop water stress index to estimate grain yield and water productivity of maize and black gram in the climatic conditions of Urmia (Iran), research was conducted under the conditions of single-row drip irrigation. This study was conducted in a randomized complete block design with four irrigation levels including 50 (I 1), 75 (I 2), 100 (I 3) and 125 (I 4) percent of the water requirements of the plants with three replications. The mean crop water stress index values for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The GT-biplot analysis also showed that CT was negatively correlated with GMP, STI, MP, HM, WP, Yp, and Ys. Therefore, CT measurement should be introduced as a practical and immediate method to evaluate the drought tolerance of rice genotypes (Yan et al, 2012;Khorsand et al, 2020;Teymoori et al, 2020). Similar to the present study, Sharifi and Ebadi (2018) and Sabouri et al (2022) also used a GT-biplot analysis to identify superior rice genotypes under drought stress conditions.…”
Section: Figmentioning
confidence: 78%
See 2 more Smart Citations
“…The GT-biplot analysis also showed that CT was negatively correlated with GMP, STI, MP, HM, WP, Yp, and Ys. Therefore, CT measurement should be introduced as a practical and immediate method to evaluate the drought tolerance of rice genotypes (Yan et al, 2012;Khorsand et al, 2020;Teymoori et al, 2020). Similar to the present study, Sharifi and Ebadi (2018) and Sabouri et al (2022) also used a GT-biplot analysis to identify superior rice genotypes under drought stress conditions.…”
Section: Figmentioning
confidence: 78%
“…Since the CT depends on the transpiration rate, water absorption capacity, and water productivity, a low CT indirectly indicates the high ability of roots to absorb (Yan et al, 2012). Also, since CT is correlated with crop RWC and yield, genotypes with a lower CT show an improved water potential and will have more tolerance to drought stress (Khorsand et al, 2020;Teymoori et al, 2020). 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation